Effect of frozen and fresh embryo transfers on the birthweight of live-born twins. (March 2020) - Chen, Linjun; Ni, Xiaobei; Xu, Zhipeng; Fang, Junshun; Zhang, Ningyuan; Li, Dong
Abstract: Objective: To explore the influence of frozen embryo transfer (FET) and fresh embryo transfer (Fresh) on the birthweight of live-born twins. Study design: A total of 8482 live-born twins were studied. The proportions of small for gestational age (SGA) and large for gestational age (LGA), the mean birthweight and the z score of live-born twins in the two groups were compared. Multiple linear regression analysis was used to evaluate the relationship between confounding factors and the birthweight of live-born twins. Results: The proportion of SGA infants significantly decreased as BMI increased (BMI < 20, 6.1 %; 20 ≤ BMI≤25, 4.1 %; BMI > 25, 3.6 %; P< 0.05). The proportion of LGA infants significantly increased as BMI increased (BMI < 20, 20.5 %; 20 ≤ BMI≤25, 25.2 %; BMI > 25, 30.7 %; P< 0.0001). The proportion of SGA infants was significantly lower in the FET group than in the Fresh group, whereas the proportion of LGA infants was significantly higher in the former than in the latter. The absolute mean birthweight of live-born twins was significantly higher in the FET group compared with the Fresh group (2579 ± 458 vs. 2534 ± 465, P  < 0.0001). The mean z score of the FET group was also significantly higher than that of the Fresh group (0.420 vs. 0.240, P  < 0.0001). Multiple linear regression analysis indicated that FET was a more significant factor than fresh embryo transfer in influencing the birthweight of live-born twins. Conclusion: FET significantly increased the birthweight of live-born twins compared with fresh embryo transfer.